2020
DOI: 10.3390/ijms21061975
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin in Health and Diseases: Alzheimer’s Disease and Curcumin Analogues, Derivatives, and Hybrids

Abstract: Worldwide, Alzheimer’s disease (AD) is the most common neurodegenerative multifactorial disease influencing the elderly population. Nowadays, several medications, among them curcumin, are used in the treatment of AD. Curcumin, which is the principal component of Curcuma longa, has shown favorable effects forsignificantly preventing or treating AD. During the last decade, the scientific community has focused their research on the optimization of therapeutic properties and on the improvement of pharmacokinetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(64 citation statements)
references
References 122 publications
(234 reference statements)
0
55
0
2
Order By: Relevance
“…Curcumin, a phenolic compound, is also known as diferuloylmethane with chemical name of (1E, 6E)-1,7-bis(4-hydroxy-3-methoxyphenyl)hepta-1,6-diene-3,5-dione) ( Figure 1 ) ( Baldi et al, 2020 ; Chainoglou and Hadjipavlou-Litina, 2020 ; Salehi et al, 2020a ; Stohs et al, 2020 ). This biologically active compound occurs in high amounts in rhizome and roots of turmeric plant ( Curcuma longa ) ( Hesari et al, 2019 ).…”
Section: Curcumin: An Overview Of the Pharmacological Impacts And Limmentioning
confidence: 99%
“…Curcumin, a phenolic compound, is also known as diferuloylmethane with chemical name of (1E, 6E)-1,7-bis(4-hydroxy-3-methoxyphenyl)hepta-1,6-diene-3,5-dione) ( Figure 1 ) ( Baldi et al, 2020 ; Chainoglou and Hadjipavlou-Litina, 2020 ; Salehi et al, 2020a ; Stohs et al, 2020 ). This biologically active compound occurs in high amounts in rhizome and roots of turmeric plant ( Curcuma longa ) ( Hesari et al, 2019 ).…”
Section: Curcumin: An Overview Of the Pharmacological Impacts And Limmentioning
confidence: 99%
“…This natural molecule also exhibits antibacterial, antifungal, antiviral, antiprotozoal, and antiparasitic properties [ 12 , 13 , 14 ]. Clinical trials have demonstrated the therapeutic benefits of curcumin supplementation in patients with inflammatory diseases (arthritis, inflammatory bowel disease, peptic ulcer, and H. pylori infection), metabolic syndrome, neurodegenerative diseases, and cancer, including colorectal, pancreatic, and breast cancers [ 11 , 15 , 16 , 17 , 18 ]. Due to the wide range of biological activities of curcumin and its pleiotropic therapeutic potential, this substance has been of great interest to researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin ( 177 ), a natural phenolic compound found in the rhizome of Curcuma longa, has been used to treat various ailments in India for centuries. Structural modifications of curcumin to improve its instability and bioavailability have been an attractive strategy in new drug discovery [ 95 , 96 ]; several pyrazole-containing curcumin derivatives have showed potency for AD treatment [ 97 ]. CNB-001 ( 178 ), a pyrazole derivative of curcumin, was initially found to have broad neuroprotective activity [ 98 , 99 ].…”
Section: Applications Of Pyrazoles In Neurodegenerative Diseasesmentioning
confidence: 99%